Determinants of food and nutrition actions in primary healthcare clinics in the State of São Paulo, Brazil - Evangelista, Mayara [UNESP]; Rossato, Sinara; Ferreira, Milena [UNESP]; Negri, Flávia; de Oliveira, Maria Rita Marques [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2019)
The objective of the study was to test the link between the preparation of professionals and the operational conditions of food and nutrition actions in primary healthcare in the state of São Paulo, Brazil. This cross-sectional study involved 220 primary healthcare clinics in 65 municipalities of the state. Of the 1873 participating healthcare professionals, 71.8% reported having provided guidance on food and nutrition to different groups, ranging from 56% for pregnant women to 17% for families. Only 19% of the primary healthcare clinics employed nutritionists. Primary healthcare clinics with fewer than two partnerships with other institutions reported 28% and 41% fewer of food and nutrition actions for adults and for families, respectively. Among the variables applied to evaluate professional preparation and operational conditions, work guidance and community partnerships were important for food and nutrition actions, which remains incipient in primary healthcare.
Determinantes de las acciones de alimentación y nutrición en las clínicas de atención primaria en el estado de São Paulo, Brasil
Keywords: Food and nutrition; Food and Nutrition Education; Health education; Health promotion; Primary health care